Efforts to improve students' mathematical critical thinking ability by using Team Assisted Individualization learning model. Issue 1 (May 2021) - Marasabessy, R; Hasanah, A; Angkotasan, N
Abstract: The development of critical thinking is the goal of the Indonesian education curriculum. However, research on how to develop and improve these abilities is still rarely studied. In this article, we offer a team assisted individualization-learning model in improving critical thinking skills. The objectives of this study were (1) to describe the improvement of students' mathematical-critical thinking skills using the Team Assisted Individualization learning model, (2) To determine the increase in students' critical thinking skills after team assisted individualization learning has carried out. This study used experimental research. The subjects in this study were fourth-semester students of the Khairun University mathematics education program. The instrument used was a question describing students' mathematical-critical thinking skills. Data have been analyzed per indicator and as a whole using descriptive analysis, namely benchmark reference guidelines (PAP) scale five and Normalized Gein. Data were analyzed using the inferential analysis to determine the increase in students' mathematical critical thinking skills, namely hypothesis testing (one-sample t-test). The result of the data analysis showed an increase in students' mathematical critical thinking skills, which were interpreted moderately after implementing the assisted individualization team learning model.